2016
DOI: 10.1177/0305735615613149
|View full text |Cite
|
Sign up to set email alerts
|

The effect of background music on food pleasantness ratings

Abstract: This study investigated whether samples of pleasant, neutral and unpleasant music can impact food perception. To this end, the pleasantness of three different types of chocolate gelati (milk chocolate, dark chocolate and bittersweet chocolate) was determined using 50 participants exposed to silence (the reference condition) and three music samples differing in self-rated preference. To measure hedonic responses to the gelati samples, the Time Intensity method was utilized to derive the maximum intensity of ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 38 publications
4
53
0
Order By: Relevance
“…It has been established in our previous studies [17,18,19,20] that changes in the sensory properties of gelato do indeed vary over time when consumed while listening to music that differed in terms of its valence. This implies that the positive and negative valence of auditory stimuli may drive crossmodal associations.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…It has been established in our previous studies [17,18,19,20] that changes in the sensory properties of gelato do indeed vary over time when consumed while listening to music that differed in terms of its valence. This implies that the positive and negative valence of auditory stimuli may drive crossmodal associations.…”
Section: Introductionmentioning
confidence: 89%
“…Recently, researchers have investigated the dynamic effects of sounds on the perception of food using time intensity (TI), Temporal Dominance of Sensations (TDS) and Temporal Check-All-That-Apply (TCATA) methods. Music varying in liking has been shown to influence the flavour perception of ice cream using TI [17], TDS [18,19] and TCATA [20]. Kantono et al [18,19] also found that emotions evoked by listening to music varying in valence were found to influence flavour perception.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auditory contributions to these sensory nudges are becoming an increasingly popular topic of research [ 4 , 5 ]. In particular, literature on ambient, atmospheric, or in-store music has been robustly shown to influence a myriad of consumer behavior and perception [ 6 , 7 , 8 , 9 ]. These include manipulations of both simple (e.g., volume and tempo) and more complex (e.g., affective and genre) acoustic parameters [ 10 , 11 , 12 , 13 , 14 ], both of which can generate spontaneous feelings and physiological reactions, (“embodied meaning”), as well as cognitively prime contextual associations through semantic networks in memory (“referential meaning”) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…One branch of the literature on sonic influences on tasting has also examined the phenomenon of 'sensation transference' -addressing questions such as 'If you like the music more, do you like what you are eating/drinking more too?' (e.g., see Kantono, Hamid, Sheperd, Yoo, Carr, & Grazioli. 2015;Kantono, Hamid, Sheperd, Yoo, Grazioli, & Carr, 2016;cf.…”
Section: Introduction To the Special Issuementioning
confidence: 99%